Bone markers and osteoporosis - (:unkn) unknown (My University, 2004)
Diagnosis of a given disease is often the first step to a successful therapy. The use of biochemical markers of bone turnover in osteoporosis is becoming more important due to their capacity to give early information. Many of the new markers are proteins, peptides, or other large biomolecules, usually present at very low concentrations. Bone is a living, growing tissue that turns over at a rate of about 10% a year. It is lergely made up of collagen, that gives the bone its tensile strength and framework, and calcium phosphate, mineralized complex that hardens the framework. After age 24, bone resorption slowly begins to happen faster than bone formation. Bone loss is most rapid in women in the first few year after menopause but continues into the postmenopausal years. Loss although much slowly, also happens in men. In addition to bone porosity, the bone strength is determined by the trabecular microstructure in wich osteoclastic, and osteoblastic activities play an important role. Osteoporosis develops when bone resorption occurs too rapidly and bone formation fails to keep up. Risk factors for osteoporosis involves age, gender, ethnicity, use of certain drugs, excersize, smoking Vit D deficiency, Ca intake, sex hormones, alcohol intake etc. Mineralization markers are serum osteocalcin, bone alkaline phosphatase, serum prokollagen 1 extention peptides. Markers for the resorption of bone on the other hand are urine N-telopeptide crosslinks, urine deoxy-piridinoline, urine hydroxyproline, tartarate dependent acid phosphatase and Catepsin K. Biochemical markers of bone turnover should be used with BMD for diagnosis.
Keywords: Bone; Bone markers; Calcium and osteoporosis; Osteoporosis